THE DEVELOPMENT OF STUDENT’S LEADERSHIP READINESS ASSESSMENT INSTRUMENT IN INDONESIA - Santoso, Thomas Budi; Sudimin, Theodorus; Elyadi, Rudi (Universitas Ahmad Dahlan, 2020)
The objectives of this study were: (a) to validate a research instrument on Indonesian student leadership readiness; (b) to analyze the student leadership readiness, based on the developed instrument; and (c) to describe the student leadership education programs of some universities in Indonesia. Data collection was carried out through two stages. The first stage of data collection is conducting in-depth interviews with resource persons to compile research instruments distributed in the second stage of data collection. The second stage of data collection was in the form of distributing questionnaires to 1,742 respondents. By using factor analysis, this study succeeded in compiling a research instrument named Student's Leadership Readiness Questionnaire (SLRQ). Ultimately, by employing, the analysis of Pearson Product Moment and Cronbach Alpha, the present paper found that the design of the research instrument on student leadership readiness must first be adjusted. That is, some statement items that are declared invalid are excluded from the design of the research instrument so that the number of question items that were originally 25 statement items was reduced to 18 items. The study found as well that the average student leadership readiness in the universities involved in the study was to be high. Meanwhile, the study found that various programs are constituted as an integral part of the leadership education program. Nevertheless, it is necessary to carry out a more effective leadership education design, especially the integration of academic activities, co-curricular activities, and extra-curricular activities in an integrated manner as a whole unit of Indonesian student leadership education.